Designing for Digital Influence: The Impact of Gigi Susu's Facade on Social Media Branding - Canny Utami, I Gusti Ayu; Yogik Adnyana Putra, I Wayan; Ardiarani Utami, Ni Wayan (Malikussaleh University, Aceh, Indonesia, 2025)
This research explores the impact of interior design, specifically the façade and interior features of Gigi Susu café, on its brand identity and success in social media branding. The study examines how the café's design elements—such as facade, signage, and natural aesthetics—contribute to its visibility on platforms like Instagram and shape customer perceptions of the brand. Using a mixed-methods approach, including content analysis of Instagram posts, customer surveys, and observational studies, the research investigates the role of